FLOUTING MAXIM OF RELEVANCE IN SITUATIONAL COMEDY MALAM MINGGU MIKO 2 - Anindita, Rahmah (Universitas Gunadarma, 2020)
This research focuses on flouting relevance maxim uttered by the characters in the situational commedy of Malam Minggu Miko 2. The problems of the research are: (1) What floutings forms of relevance maxim are undergone by the characters in situational comedy Malam Minggu Miko 2? (2) What are the reasons of the characters flouting the maxims of relevance? The purposes of this research are: (1) To identify forms of flouting relevance maxims undergone by characters in situational comedy of Malam Minggu Miko 2 (2) To describe the reasons of the characters flouting the maxims of relevance. The method used in this study is descriptive qualitative method. This research used theory of Grice. Results obtained from this research show that there are fourty data that represents of flouting maxim relevance. The data divided into two forms of flouting maxim of relevance, they are to change the subject (8) and give an irrelevant statement (32) and for the reason, there are nine type of the reasons of the characters flouting the maxims of relevance there are ten data of hiding the truth (25%), two data of saving face (5%), two data of feeling jealous about something (5%), two data of convincing the hearer (5%), two data of cheering the hearer (5%), seven data of mocking someone (17%), four data of teasing the hearer (10%), five data of lacking of knowledge (13%) and six data of to showing itself (15%). The reasons that are often used in this sitcom is hiding the truth.